Health care: life stories by trans women in Colombia - Juan Carlos Zapata Mayor; Paula Andrea Hoyos Hernández (BMC, 2024)
Abstract Background In Colombia, health care for people with trans life experiences is characterised by countless barriers to health services and care. Commonly, trans people have experienced stigma and discrimination among health professionals, a lack of services and professionals specialized to guarantee affirmative processes from non-hegemonic gender perspectives, and there exists a marked pathologization and medicalization of services. Therefore, it is necessary to provide affirmative health services to improve health and well-being from the recognition of their needs and experiences. The article describes life narratives about health care for the gender transitions of trans women in Colombia. Methods A qualitative narrative study was conducted with 139 trans women in seven cities in Colombia. In-depth interviews and discussion groups were conducted between June 2019 and March 2020. Data were analyzed using thematic analysis and the Atlas Ti cloud program. National and international ethical guidelines were followed in the development of the research. Results This research provided an overview of the health experiences of Colombian trans women. They reported their experiences of pathologizing approaches to transgender healthcare, stigma, discrimination, and barriers to accessing preventive, specialized, and regular healthcare services. For this reason, they opted for self-medicated gender transition processes and self-management of health care. An important aspect to consider within healthcare is that not all women want binary gender transition processes. Conclusion Participants felt that in Colombia there is a lack of affirmative health care for transgender women and that there are many limitations to care related to the gender transition processes. This exposes them to more situations that violate their rights and influences their lack of confidence and their search for professional health care. In Colombia, it is important to develop strategies for education, information, and communication, as well as a handbook for health workers on specialized healthcare for trans women.